Dynamics of Micro-Rheological Properties of Red Blood Cells in Animals on the Background of Hypothermia (Indian Journal of Public Health Research & Development, 2020)
Context: Purpose: to find out age-related changes in the micro-rheological characteristics of red blood cellsin rats after hypothermia. The study included 88 healthy outbred male rats at the age of 6 months. Prior toinclusion in the study, all rats were healthy and did not participate in the studies. Animals experienced anepisode of hypothermia - within 1 hour at a temperature of -10º?. The control group consisted of 32 healthyoutbred male rats of a similar age. The study was conducted using biochemical, hematological and statisticalresearch method. In rats subjected to hypothermia, an increase in the activity level of free radical oxidationprocesses in plasma lipids and red blood cells was found. Over time, a decrease in the level of erythrocytediscocyteswas observed in the blood of the observed rats, which was most pronounced in rats one monthafter hypothermia. This was accompanied by an increase in their level of changed reversibly and irreversiblyerythrocyte forms and an increase in spontaneous aggregation of red blood cells. In rats, after an episode ofhypothermia, a gradual weakening of the plasma antioxidant defense develops. In these rats, aggregationreadiness and the degree of change in the surface properties of red blood cells progressively increased.Apparently, this creates a risk in animals of a progressive increase in morbid burden and weakening of thewhole organism in relation to resistance to negative environmental influences.
Keywords: Rats, hypothermia, red blood cells, cytoarchitectonics, aggregation